Program Tahfidzul Qur’an TPQ Al-Ikhlas Gunungan Dawarblandong Mojokerto - Yana Eka Endar Sari; Nanang Abdillah (LPPM STAI Al-Azhar Menganti Gresik, 2022)
This study aims to: 1) Know the implementation of the Qur'an tahfidz program at TPQ Al-Ikhlas Gunungan Dawarblandong Mojokerto. 2) Knowing the obstacles to implementing the Qur'an tahfidz program at TPQ Al-Ikhlas Gunungan Dawarblandong. The type of research used in this study is a descriptive qualitative approach and the type of field research using the case study method. The results of this study are 1) In the implementation of the tahfidzul Qur'an program, there are 3 stages, namely the first planning. At the planning stage, the clerics prepare rote planning according to the predetermined curriculum. Then the implementation stage, the tahfidzul Qur'an program is carried out every day for private recitals. The last is the evaluation stage, with the tahfidzul Qur'an program making students more diligent in reading the Koran and reading the Koran. 2) The obstacles experienced when implementing the tahfidzul Qur'an program were that some students still had difficulty memorizing.